2010
DOI: 10.1186/1471-2199-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human Activin-A receptor type II-like kinase 1 (ACVRL1) promoter and its regulation by Sp1

Abstract: BackgroundActivin receptor-like kinase 1 (ALK1) is a Transforming Growth Factor-β (TGF-β) receptor type I, mainly expressed in endothelial cells that plays a pivotal role in vascular remodelling and angiogenesis. Mutations in the ALK1 gene (ACVRL1) give rise to Hereditary Haemorrhagic Telangiectasia, a dominant autosomal vascular dysplasia caused by a haploinsufficiency mechanism. In spite of its patho-physiological relevance, little is known about the transcriptional regulation of ACVRL1. Here, we have studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“…These data suggest that specific methylation of the CpG dimer in position 66 may be important for regulation of Serca2a transcriptional activity. This result is supported by other studies reporting methylation of CpG dimers adjacent to SP1 DNA binding sites reduced SP1 binding [16,43,44]. In particular, Kitazawa et al [27] reported that in rat leukemia cell lines, methylation that was not within but adjacent to the two SP1 sites in the promoter significantly reduced cyclin D expression.…”
Section: Discussionsupporting
confidence: 70%
“…These data suggest that specific methylation of the CpG dimer in position 66 may be important for regulation of Serca2a transcriptional activity. This result is supported by other studies reporting methylation of CpG dimers adjacent to SP1 DNA binding sites reduced SP1 binding [16,43,44]. In particular, Kitazawa et al [27] reported that in rat leukemia cell lines, methylation that was not within but adjacent to the two SP1 sites in the promoter significantly reduced cyclin D expression.…”
Section: Discussionsupporting
confidence: 70%
“…The ALK1 gene contains 14 transcription factor binding sites for SP1, 1 Smad binding element, 7 for RXR dimers and 3 hypoxia inducible factor consensus binding sites. The promoter and enhancer regions are highly conserved throughout species and can be methylated to regulate gene expression [34]. The regulatory elements for arterial expression of ALK1 is located within a 9.3 kb genomic fragment, which contains the entire intron 2 and a 2.7 kb promoter region [35].…”
Section: Alk1 Gene Structure and Regulationmentioning
confidence: 99%
“…However, utility of this approach (as well as several other approaches discussed above) is predicated on the assumption that HHT vascular lesions result from haploinsufficiency and not dominant negative protein activity or a second somatic hit. Arterial endothelial-specific Acvrl1 expression in mice requires an enhancer in the equivalent of human ACVRL1 intron 1 [129], and transcription factors SP6 and KLF6 regulate ACVRL1 expression via sites in the proximal promoter [130,131]. In mice and zebrafish, Acvrl1 is regulated by blood flow/ mechanical force, although the underlying molecular mechanism is unknown [54,98].…”
Section: Medical Therapies For Hht: Current Practice and Future Perspmentioning
confidence: 98%